2021
DOI: 10.1038/s41598-021-84325-3
|View full text |Cite
|
Sign up to set email alerts
|

Attentional and cognitive monitoring brain networks in long-term meditators depend on meditation states and expertise

Abstract: Meditation practice is suggested to engage training of cognitive control systems in the brain. To evaluate the functional involvement of attentional and cognitive monitoring processes during meditation, the present study analysed the electroencephalographic synchronization of fronto-parietal (FP) and medial-frontal (MF) brain networks in highly experienced meditators during different meditation states (focused attention, open monitoring and loving kindness meditation). The aim was to assess whether and how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…That paper cited research from the broader fields of cognitive and affective neuroscience, as well as from the field of CoNS, which supported the notion that these enhanced cognitive, affective, and null states demonstrated distinctly different and measurable neurophysiological correlates (e.g., Lehmann et al, 2001;Dalgleish, 2004;Carter et al, 2005;Cahn and Polich, 2006;Hankey, 2006;Holzel et al, 2007Holzel et al, , 2008Lutz et al, 2007Lutz et al, , 2008Davidson, 2010;Travis and Shear, 2010;Josipovic et al, 2011;Leung et al, 2013). 8 Since then, our original thesis has been supported by more recent research as well (e.g., Dahl et al, 2015;Brandmeyer et al, 2019;Josipovic, 2019;Raffone et al, 2019;Afonso et al, 2020;Yordanova et al, 2020Yordanova et al, , 2021. Lee et al (2012, p.7) concluded that "different forms of meditation have meditation-specific effects on neural activity, rather than a common neural mechanism"; "different forms of meditation practice create domain-specific plastic changes in neural activity"; and "each form of meditation is associated with a dissociable pattern of neural activity."…”
Section: Supportive Neuroscientific Findingsmentioning
confidence: 57%
See 2 more Smart Citations
“…That paper cited research from the broader fields of cognitive and affective neuroscience, as well as from the field of CoNS, which supported the notion that these enhanced cognitive, affective, and null states demonstrated distinctly different and measurable neurophysiological correlates (e.g., Lehmann et al, 2001;Dalgleish, 2004;Carter et al, 2005;Cahn and Polich, 2006;Hankey, 2006;Holzel et al, 2007Holzel et al, , 2008Lutz et al, 2007Lutz et al, , 2008Davidson, 2010;Travis and Shear, 2010;Josipovic et al, 2011;Leung et al, 2013). 8 Since then, our original thesis has been supported by more recent research as well (e.g., Dahl et al, 2015;Brandmeyer et al, 2019;Josipovic, 2019;Raffone et al, 2019;Afonso et al, 2020;Yordanova et al, 2020Yordanova et al, , 2021. Lee et al (2012, p.7) concluded that "different forms of meditation have meditation-specific effects on neural activity, rather than a common neural mechanism"; "different forms of meditation practice create domain-specific plastic changes in neural activity"; and "each form of meditation is associated with a dissociable pattern of neural activity."…”
Section: Supportive Neuroscientific Findingsmentioning
confidence: 57%
“…Since then, our original thesis has been supported by more recent research as well (e.g., Dahl et al, 2015 ; Brandmeyer et al, 2019 ; Josipovic, 2019 ; Raffone et al, 2019 ; Afonso et al, 2020 ; Yordanova et al, 2020 , 2021 ). Lee et al (2012 , p.7) concluded that “different forms of meditation have meditation-specific effects on neural activity, rather than a common neural mechanism”; “different forms of meditation practice create domain-specific plastic changes in neural activity”; and “each form of meditation is associated with a dissociable pattern of neural activity.” In a review of meditation research findings to date, Travis concurs: “the assumption that a common brain marker would emerge by combining different meditation practices together in one analysis is flawed.…”
Section: Supportive Neuroscientific Findingsmentioning
confidence: 75%
See 1 more Smart Citation
“…Where Cov(i,j) is the cross-spectral density between two signals, and Var(i)and Var(j) are the auto spectral densities for signals i and j, respectively. The correlation value lies between +1 to -1, where +1 indicates that signals are perfect positive correlation, -1 indicates a perfect negative correlation, and 0 indicates that the two signals are perfectly uncorrelated [18,26] .…”
Section: Eeg Acquisition and Segmentationmentioning
confidence: 99%
“…Functional connectivity can be used for analyzing cognitive activity [11], disorders like schizophrenia [12], depression [13], chronic pain [14], yoga, and meditation [15][16][17]. Therefore, we have used functional connectivity parameters in the present study such as Pearson correlation (r) [18], phase locking value (PLV) [19], clustering coefficient (CC), and shortest path (SP) [20]. Previous meditation reported an increase in functional connectivity of the brain during meditation as compared to the resting state [21].…”
Section: Introductionmentioning
confidence: 99%